Animal Performance and Carcass Characteristics of Crossbred Bulls Finished in Different Production Systems in the Tropics - Jean Fagner Pauly; Jéssica Geralda Ferracini; Henrique Rorato Freire; Bianka Rocha Saraiva; Maribel Valero Velandia; Ana Guerrero; Rodolpho Martin do Prado; Ivanor Nunes do Prado (Applied Sciences)
Extensive beef systems in the tropics are the cheapest but require more land and longer rearing times with environmental impact. This study was carried out to evaluate three beef bull’s production systems in tropics: pasture-based system (PASTU), feedlot system immediately after weaning (FELOT) and a system with the combination of rearing in pasture and finishing in feedlot (PRIME) on animal performance and carcass characteristics of 30 bulls crossbred Angus x Nellore. The final weight, average daily gain and carcass weight (hot and cold) were higher (p < 0.050) for the FELOT system, intermediate for the PRIME system and lowest for the PASTU system. The carcass dressing (hot and cold), dripping losses, ratio (Longissimus dorsi) and degree of finishing were similar (p > 0.050). The carcass pH24h was higher for the PRIME system (p < 0.010). Subcutaneous fat thickness (mm) was lower for the PASTU system (p < 0.050). Marbling was better for the PRIME system. The tissular composition was similar among systems related to muscle percentage but PASTU showed the highest bone percentage (p < 0.050) and lowest of adipose (p < 0.050). PRIME enable cost-effective, fast beef production with less environmental impact.